Seattle's Plenty Good Enough for Me - A.J.R.
1908 In 1908, Seattle had seen eleven years of prosperity, which had begun with the 1897 arrival of the first shipment of gold from the Yukon gold fields."Seattle's Plenty Good Enough for Me" was one of a number of songs written at that time promoting the Pacific Northwest's good climate for business and trade. The cover shows a band member blaring out the tune on his trumpet. In the background are several tree stumps, possibly representing the lumber industry, as well as a shelter and a version of a totem pole. The composer and lyricist for "Seattle's Plenty Good Enough for Me" is identified only as A.J.R. The score was published by Vashon Island Printing Company and printed by Rayner & Daheim Lithographers of Chicago. 1 score (6 p.) + 1 part 10.5 x 13.75 in.